The class dynamics of income shares: effects of the declining power of unions in the US airline industry, 1977–2005. (23rd November 2017) - Avent-Holt, Dustin
Abstract: Although class relations are situated within workplaces, research on class income shares has neither examined firm-level mechanisms nor distinguished between managerial and non-managerial workers within the class of labor. This article analyzes the effects of union power on the distribution of shares of income between capital, top managers, and non-managerial workers at the firm-level during the neoliberal era. Using data on US airlines from 1977 to 2005 I find that strikes are central to shaping the firm-level distribution of income shares, but in an unexpected way. Strikes redistribute income away from non-managerial workers, without affecting either profit or top managerial income shares. These results suggest that analyses of income distribution across classes must incorporate a more detailed class schema as well as observe effects of deunionization at the firm level. Moreover, the findings provide further evidence that firm-level mechanisms are shaped by the institutional context in which firms operate.